The Role of E-WOM, Perceived Price, and Perceived Quality in Building Brand Image and Visit Intention at SANS Hotel RedDoorz Jakarta among the Young Generation - Safitri Eka Lestari; Usep Suhud; Nofriska Krissanya (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of writing this research is to examine the role of E-WOM, perceived price, and perceived quality in building brand image and its impact on visit intention. Data collection was carried out using a questionnaire method distributed online through social media. The objects taken in this study are potential customers who know about SANS Hotel RedDoorz, live in Jakarta, and are part of the younger generation (at least 17 years old). The sample used in this study totalled 277 respondents. This research uses SEM (Structural Equation Model) with the help of AMOS software to carry out the data analysis and processing process. It is hoped that the results obtained in this study can provide new insights and become a reference for further research. The results obtained in this study show that E-WOM, perceived price, and perceived quality have a positive and significant effect on brand image. In addition, all of these variables along with brand image are also proven to have a positive and significant effect on visit intention.